2017
DOI: 10.1007/s11999-016-5188-2
|View full text |Cite
|
Sign up to set email alerts
|

Is There Asymmetry Between the Concave and Convex Pedicles in Adolescent Idiopathic Scoliosis? A CT Investigation

Abstract: There is clinically important asymmetry in the morphologic features of pedicles in individuals with adolescent idiopathic scoliosis. The concave side of the curve compared with the convex side is smaller in height and width periapically. Furthermore, the trajectory of the pedicle is more acute on the convex side of the curve compared with the concave side around the apex of the curve. Knowledge of these anatomic variations is essential when performing scoliosis correction surgery to assist with selecting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
2
31
0
5
Order By: Relevance
“…Pedicle width is widely accepted as the limiting factor in screw-caliber selection owing to its smaller size compared with other diameters of the pedicle [12,31]. Similar to previous studies [2,4,9,31,37], we found PWc to be narrower than PWv. In addition, our results showed that there was no difference between PWv and PWn, indicating that the concave side is the dysplastic side of the curve, while the pedicles on the convex side seem to be normal.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pedicle width is widely accepted as the limiting factor in screw-caliber selection owing to its smaller size compared with other diameters of the pedicle [12,31]. Similar to previous studies [2,4,9,31,37], we found PWc to be narrower than PWv. In addition, our results showed that there was no difference between PWv and PWn, indicating that the concave side is the dysplastic side of the curve, while the pedicles on the convex side seem to be normal.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is important that spinal surgeons have clear knowledge of the morphometric anatomy of pedicles, especially in deformed spines, to guarantee the safest pedicle screw placement. Using CT scans, we conducted a morphologic study of thoracic pedicles in 60 female patients with Lenke Type 1 adolescent idiopathic scoliosis and 60 sex-, age-, and height-matched controls, which provided a more-accurate assessment than previously published studies because of our large sample size and sample homogeneity [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the pedicles in the concave side were even too narrow to accommodate the inserted screw. In addition, a smaller pedicle consists of a higher proportion of cortical bone [2, 14, 15]. A slow advance of the drill while maintaining high revolutions per minute is another method to prevent trajectory deviation.…”
Section: Discussionmentioning
confidence: 99%
“…13 CT has been used to evaluate coronal curvature with a small error of measurement (<2.7°), 13 and AVR 14,15 with high reliability (intraclass correlation coefficient = 0.95) 14 . It has also been used to investigate the asymmetry of vertebral body 16 and pedicles, 16,17 as well as anterior-posterior length 18 of the spinal column. However, it has never been used to measure the PMC.…”
Section: Introductionmentioning
confidence: 99%